Host Cell Death Responses to Non-typhoidal Salmonella Infection - Wemyss, Madeleine A.; Pearson, Jaclyn S. (Frontiers in Immunology, 2019)
Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) is a Gram negative bacterium with a broad host range that causes non typhoidal salmonellosis in humans. S. Typhimurium invades epithelial cells and macrophages in the small intestine where it replicates in a specialized intracellular niche called the Salmonella-containing vacuole (SCV) and promotes inflammation of the mucosa to induce typically self-limiting gastroenteritis. Virulence and spread of the bacterium is determined in part by the host individual’s ability to limit the infection through a combination of innate immune and programmed cell death responses at the gastrointestinal mucosa. S. Typhimurium however, has evolved a myriad of mechanisms to counteract or exploit host responses through the use of Type III Secretion Systems (T3SS), which allow the translocation of virulence (effector) proteins into the host cell for the benefit of optimal bacterial replication and dissemination. T3SS effectors have been found to interact with apoptotic, necroptotic and pyroptotic cell death cascades, interfering with both efficient clearance of the bacteria and the recruitment of neutrophils or dendritic cells to the area of infection. The interplay of host immunity, programmed cell death responses and bacterial defenses in the context of non-typhoidal Salmonella infection is a continuing area of interest within the field, and as such has been reviewed here.